A crítica de Edward Stillingfleet à teoria lockiana da substância - Carlota Salgadinho Ferreira; Vinícius França Freitas (O Que Nos Faz Pensar)
We intend to present an interpretation of the dispute between John Locke and Edward Stillingfleet, Bishop of Worcester, regarding the notion of substance. First, we present some of Locke’s claims that justify Stillingfleet’s skeptical reading of Locke’s treatment of substance. Secondly, we claim that Stillingfleet neglects Locke’s distinction between two notions of substance. Thirdly, we present three hypotheses regarding some claims that Locke and Stillingfleet seems to share about the nature of substance. Fourthly, we argue that Locke is not a skeptical about the existence of substances, although he is committed to the view that the understanding only has a confused and obscure idea of it. Finally, we claim that Stillingfleet neglects that Locke is committed with the experimental method of reasoning in his treatment of substance. In the end, we conclude that Stillingfleet’s view on substance has more in common with that of Locke’s than he realizes.